2018
DOI: 10.1108/ijlss-11-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Application of Six Sigma DMAIC methodology in plain yogurt production process

Abstract: Purpose This study aims to concentrate on quality improvement in plain yogurt production process at company A through adjusting the factors affecting the acidity of the yogurt and determining the optimal level of these factors. Design/methodology/approach Six Sigma-based framework using define-measure-analyze-improve-control (DMAIC) methodology is adopted through the application of design of experiments tool to focus on customer’s requirements to improve the quality characteristic of plain yogurt production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 41 publications
1
36
0
4
Order By: Relevance
“…The company advantage in applying this method can reduce costs tremendously [18]. This method is still developing in increasing productivity in the food and beverage industry [19], [20] and optimizing the production process in the textile industry [21]. The Six Sigma DMAIC method focuses on reducing process variability to produce high-quality products and creating an efficient process obtained without waste, resulting in added value for customers [22].…”
Section: Fig 1 Roof Panel Partmentioning
confidence: 99%
“…The company advantage in applying this method can reduce costs tremendously [18]. This method is still developing in increasing productivity in the food and beverage industry [19], [20] and optimizing the production process in the textile industry [21]. The Six Sigma DMAIC method focuses on reducing process variability to produce high-quality products and creating an efficient process obtained without waste, resulting in added value for customers [22].…”
Section: Fig 1 Roof Panel Partmentioning
confidence: 99%
“…There are several factors which could potentially influence the quality of cast lead sheets and promote the formation of grooves. Hence, based on process observation, literature review [12,22,23] and the experience of foundry engineers, all the possible factors affecting the quality of sheets were categorised based on a 5 M model (Man, Material (Melt), Machine (Mould), Method, Measurement) and environment [24] (see Table 2). There are several factors which could potentially influence the quality of cast lead sheets and promote the formation of grooves.…”
Section: Defect Analysismentioning
confidence: 99%
“…Previous research that used the SS method/approach showed that it was a significant method to decrease defects (Hakimi et al, 2018). This method is still developing to reduce costs and increase productivity in the food industry (Costa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%